Sustainable Development Goals: Polemic Study of Analysis of Environmental Impacts After Perppu Cipta Kerja - Siagian, Abdhy Walid; Fajar, Habib Ferian; Alify, Rozin Falih (Ikatan Penulis Mahasiswa Hukum Indonesia Law Journal, 2023)
Government Regulation instead of Law No. 2 of 2022 concerning Job Creation (Perppu Cipta Kerja) narrows the community's space for movement and injustice in preparing an Environmental Impact Analysis (AMDAL). To answer this, the principle is reduced Sustainable Development Goals, which is believed to be able to answer various problems and challenges of environmental development and development. This study aims to determine the nature of community participation in the EIA process according to the principles of sustainable Development Goals. This research process will use a normative juridical method, with an approach statute approach and a conceptual approach. The presence of the Job Creation Perppu places limitations on the role of the community in preparing the EIA, which is contrary to the concept of Sustainable Development Goals.